2010
DOI: 10.1080/09541440903126030
|View full text |Cite
|
Sign up to set email alerts
|

“I see what you mean”: Oral deaf individuals benefit from speaker's gesturing

Abstract: Recent studies in the psychological literature reveal that cospeech gestures facilitate the construction of an articulated mental model of an oral discourse by hearing individuals. In particular, they facilitate correct recollections and discourse-based inferences at the expense of memory for discourse verbatim. Do gestures accompanying an oral discourse facilitate the construction of a discourse model also by oral deaf individuals trained to lip-read? The atypical cognitive functioning of oral deaf individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…In line with such view, we argue that co-speech gestures, which are spatial in nature, convey information that can be easily incorporated into the text/discourse mental model because mental models themselves are spatially organized (Knauff & Johnson-Laird, 2002); moreover, gestures are cast in the same non-discrete representational format as mental models. Previous studies have shown that co-speech gestures performed by the speaker facilitate the construction of an articulated mental model by the listener (Cutica & Bucciarelli, 2008, 2011; this also holds for oral deaf individuals trained to lip-read: Vendrame, Cutica & Bucciarelli, 2010). A better mental model results in a greater number of correct recollections and correct inferences drawn from the information explicitly contained in the discourse, and poorer retention of surface information (verbatim).…”
Section: The Facilitating Effect Of Gesture Observation and Gesture Pmentioning
confidence: 87%
“…In line with such view, we argue that co-speech gestures, which are spatial in nature, convey information that can be easily incorporated into the text/discourse mental model because mental models themselves are spatially organized (Knauff & Johnson-Laird, 2002); moreover, gestures are cast in the same non-discrete representational format as mental models. Previous studies have shown that co-speech gestures performed by the speaker facilitate the construction of an articulated mental model by the listener (Cutica & Bucciarelli, 2008, 2011; this also holds for oral deaf individuals trained to lip-read: Vendrame, Cutica & Bucciarelli, 2010). A better mental model results in a greater number of correct recollections and correct inferences drawn from the information explicitly contained in the discourse, and poorer retention of surface information (verbatim).…”
Section: The Facilitating Effect Of Gesture Observation and Gesture Pmentioning
confidence: 87%
“…Comprehension of co-speech gestures has been researched more extensively in DHH individuals than comprehension of other gesture types because of their supporting role in language processing (Krauss et al, 1991;McNeill, 1994;Kelly et al, 2010b). In oral-deaf individuals who tend to be born to hearing parents and learn to communicate orally and to read words on the lips of the speakers (Vendrame et al, 2010), gestures accompanying discourse facilitate retention of content information and correct inferences. However, co-speech gestures interfere with verbatim memory for discourse in these individuals.…”
Section: Gesture Comprehension and Use In The Dhh Populationmentioning
confidence: 99%